Gamification as a pedagogical strategy to enhance cognitive, affective, and academic engagement in higher education - Ygnacio Tomaylla-Quispe; Olger Gutiérrez-Aguilar; Sandra Chicana-Huanca (Intelektual Pustaka Media Utama, 2026)
This study investigates how gamification influences student engagement in fully distance higher education, distinguishing academic, cognitive, and affective engagement. Using survey data from 234 undergraduates, we tested a structural model linking motivational and social gamification components (motivation, teamwork, peer interaction, and teacher participation) to engagement outcomes. Results show that motivation predicts academic and cognitive engagement, while teacher participation is the strongest driver of affective engagement; affective engagement, in turn, strengthens cognitive engagement. Teamwork contributes positively across engagement dimensions, whereas peer interaction is not significant in this distance-learning context. By modeling engagement as a multidimensional construct and separating specific gamification components, this study clarifies why some gamified mechanisms work better than others online. Practically, effective gamified course design should prioritize instructor presence and structured teamwork alongside motivational elements to sustain engagement in virtual higher education.